2021
DOI: 10.1038/s41598-021-96586-z
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil to lymphocytes ratio is associated with nutritional risk in hospitalised, unselected cancer patients: a cross-sectional study

Abstract: Cancer patients possess metabolic and pathophysiological changes and an inflammatory environment that leads to malnutrition. This study aimed to (i) determine whether there is an association between neutrophil-to-lymphocyte ratio (NLR) and nutritional risk, and (ii) identify the cut-off value of NLR that best predicts malnutrition by screening for nutritional risk (NRS 2002). This cross-sectional study included 119 patients with unselected cancer undergoing chemotherapy and/or surgery. The NRS 2002 was applied… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 19 publications
(34 reference statements)
0
8
0
Order By: Relevance
“…Therefore, we cannot establish temporality, and we encourage readers to interpret this finding with caution. Indeed, nutrition risk is associated with increased NLR ( 60 ), but nutitional status was not assessed in this study, and BMI at diagnosis is not an indicator of nutritional risk.…”
Section: Discussionmentioning
confidence: 86%
“…Therefore, we cannot establish temporality, and we encourage readers to interpret this finding with caution. Indeed, nutrition risk is associated with increased NLR ( 60 ), but nutitional status was not assessed in this study, and BMI at diagnosis is not an indicator of nutritional risk.…”
Section: Discussionmentioning
confidence: 86%
“…Numerous scientific data have confirmed that nutritional status and sarcopenia are associated with NLR, a marker of systemic inflammation (Siqueira et al , 2021; Öztürk et al , 2018). Recently, a community-based cross-sectional study in Japanese older adults has showed that a higher NLR is associated with poorer physical functions such as lower HGS and slower walking speed (Yoshida et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…However, it should be known that age, gender, exogenous steroid use, hematological disorders and chemotherapy can significantly affect NLR (Bedel and Korkut, 2021; Buonacera et al , 2022). Studies have suggested that NLR is associated with nutritional risk in critical illness (Siqueira et al , 2021; Wang et al , 2022). However, it is not clear whether the increase in NLR is a cause or a consequence of malnutrition in older adults.…”
Section: Introductionmentioning
confidence: 99%
“…24 Siqueira et al recently reported that systemic inflammation assessed using the neutrophilto-lymphocyte ratio (NLR) was associated with nutritional risk. 25 The Global Leadership Initiative on Malnutrition (GLIM) also included inflammation as one important etiologic criterion for malnutrition diagnosis. 26 In the present study, NIPGS incorporating shown GLIM-defined malnutrition is a reliable predictor of survival in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%